1999
DOI: 10.1034/j.1600-0420.1999.770426.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital retinal macrovessels, A "low visual acuity" case report with a 14-year follow-up

Abstract: ABSTRACT. We report a rare case of congenital retinal macrovessel with decreased visual acuity, with a 14-year follow-up. Both the clinical findings and the visual acuity remained unchanged throughout the follow-up period.Key words: Congenital retinal macrovessels -decreased visual acuity -retinal fluorangiographycilioretinal artery.Acta Ophthalmol. Scand. 1999; 77: 474-475 Copyright c Acta Ophthalmol Scand 1999. ISSN 1395-3907A 5-year-old child was seen by us in September 1984. Visual acuity was 20/40 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…CRM in this patient had two another atypical feature. First, the macrovessel is usually seen to circumscribe around the foveola and rarely pass through its centre 4 10–12. However, the macrovessel passed through the centre of the FAZ in this patient.…”
Section: Discussionmentioning
confidence: 75%
“…CRM in this patient had two another atypical feature. First, the macrovessel is usually seen to circumscribe around the foveola and rarely pass through its centre 4 10–12. However, the macrovessel passed through the centre of the FAZ in this patient.…”
Section: Discussionmentioning
confidence: 75%
“…Brown et al first reported seven eyes with CRM having normal vision [ 4 ]. De Crecchio et al followed a case with impaired but stable visual acuity over 14 years [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 Involvement of the fovea may determine a reduction of visual acuity, stable at longterm follow-up. 2 Visual impairment has been generally attributed without any significant evidence to the mere presence of the macrovessel in the foveal area, rather than to an anomalous development of the neuroretina caused by the abnormal vessel. 2,4,5 Nevertheless, in these reports, no OCT had been performed.…”
Section: Commentmentioning
confidence: 99%
“…2 Visual impairment has been generally attributed without any significant evidence to the mere presence of the macrovessel in the foveal area, rather than to an anomalous development of the neuroretina caused by the abnormal vessel. 2,4,5 Nevertheless, in these reports, no OCT had been performed. In this reported case, live microstructural evaluation with OCT has shown non-oedematous foveal thickening and a high-tomedium hyper-reflective area near the vessel that distorted the retinal architecture.…”
Section: Commentmentioning
confidence: 99%